Infinite Servers Queue Systems Busy Period Time Length Distribution and Parameters Study through Computational Simulation - Ferreira, M. A. M. (CoRR, VOLUME: abs/2110.09526, 2025)
A FORTRAN program to simulate the operation of infinite server's queues presented in this work. Poisson arrivals processes are considered but not only. For many parameters of interest in queuing systems study or application, either there are not theoretical results or, existing, they are mathematically intractable what makes their utility doubtful. In this case a possible issue is to use simulation methods in order to get more useful results. Indeed, using simulation, some experiences may be performed and the respective results used to conjecture about certain queue systems interesting quantities. In this paper this procedure is followed to learn something more about quantities of interest for those infinite servers queue systems, in particular about busy period parameters and probability distributions.